THE SECURITY SYSTEM IN THE STATE OF PHARAOH BETWEEN OPPRESSION AND PENETRATION IN LIGHT OF QURANIC TEXTS) - Karim, Qais Jalil; Ali Al-Ani, Qasim Salih (International Journal of Psychosocial Rehabilitation, 2020)
This paper highlights the manifestations of violence, oppression, and terrorism in the mighty Pharaoh's state that was one of the most powerful states in oppression and terrorism mentioned by the Great Qur’an. It is represented by Pharaoh, the leader of the security system of the state characterized by the most terrible descriptions, and his minister, Haman, who is no less brutal and tyrannical, as well as Qarun the usurper for people's money, wealth, and the servile army. The Quranic texts came with very precise and eloquent words, which we tried to open their secrets and intentions with the help of interpreters and writers in the discipline of the Qur’an sciences. In spite of the oppression and tyranny of this state, there was a security breach in it. Musa, peace be upon him, entered the criminal leader’s house while he was unaware of a group of believers specially a believer from the Pharaoh’s family who kept his faith secret”, the security system leader’s wife who believed secretly, pharaoh’s daughter(Mashitta) and others who were not mentioned in the books of interpretation, biography, history and the Great Qur’an.